FAKTOR KETERLAMBATAN KEDATANGAN KERETA API PENUMPANG DAN KINERJA DAERAH OPERASI 1 JAKARTA - Masjraul Hidayat; Djayo Anggoro; Sarinah Sarinah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this study is to analyze the delay arrival of passenger trains towards the operation performance of Jakarta first district operation. The problem of this study is the delay arrival of the passenger trains and the operation performance of Jakarta first district operation. The data collection used an unstructured interview method, library research, and the company’s data. The data was analyzed with a simple linear regression method and the basic calculation of the delay arrival of passenger trains and the operation performance. The result of the delay arrival of passenger trains (X) towards the operation performance of Jakarta first district operation (Y) is 38.44%, in which the result of the interpretation towards the correlation coefficient is 0.62. The result shows a strong correlation.